Pengembangan Media Pembelajaran Pada Mata Kuliah Analisa Struktur Di Jurusan Pendidikan Teknik Sipil Dan Perencanaan Universitas Negeri Makassar - Sari, Fajrianti; Pertiwi, Nurlita; Natsir, Taufiq (Universitas Negeri Makassar, 2023)
Study this aim for developing learning media eye Structural Analysis course special static portal material no of course with method style . Subject in study this is students who program eye Structural Analysis course , and the object of research this is a learning medium interactive in the form of percentage materials and examples matter . Research results show that the media developed